Effects of Temperature on Para rubber (Hevea brasiliensis Müell. Arg.) Leaf Photosynthesis Rates at Different Ambient CO2 Concentrations - thabkhum, Rungtawan; Kositsup, Boonthida; Sonjaroon, Weerasin; Satakhun, Duangrat; Sathornkich, Jate; Chayawatand, Chompunut; Dunangnam, Orunma; Kasemsap, Poonpipope (Science Essence Journal, 2020)
บทคัดย่อ งานวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาอิทธิพลของอุณหภูมิต่ออัตราการสังเคราะห์ด้วยแสงของใบยางพาราที่ความเข้มข้นของก๊าซคาร์บอนไดออกไซด์ต่างๆ โดยวัดการตอบสนองต่อความเข้มข้นของก๊าซคาร์บอนไดออกไซด์ของอัตราการสังเคราะห์ด้วยแสงสุทธิของใบที่อุณหภูมิต่างๆ ในห้องควบคุมอุณหภูมิ กำหนดความเข้มแสง 1,400 µmol m-2 s-1 ความชื้นสัมพัทธ์ระหว่าง 50-80 เปอร์เซ็นต์ ภายใต้อุณหภูมิ 9 ระดับ คือ 10, 15, 22, 28, 32, 36, 40, 42 และ 45 องศาเซลเซียส จากนั้นวิเคราะห์ข้อมูลการตอบสนองของอัตราการสังเคราะห์ด้วยแสงสุทธิต่ออุณหภูมิใบ โดยใช้สมการ 4th order polynomial equation และประเมินอุณหภูมิที่เหมาะสมต่ออัตราการสังเคราะห์ด้วยแสงสุทธิของใบที่ความเข้มข้นของก๊าซคาร์บอนไดออกไซด์ในระดับต่างๆ ผลการทดลองพบว่า สมการ 4th order polynomial equation อธิบายความแปรปรวนของการตอบสนองต่ออุณหภูมิของอัตราการสังเคราะห์ด้วยแสงสุทธิได้ดี การเปลี่ยนแปลงความเข้มข้นของก๊าซคาร์บอนไดออกไซด์ทำให้การตอบสนองต่ออุณหภูมิของอัตราการสังเคราะห์ด้วยแสงสุทธิของใบเปลี่ยนแปลงไป เมื่อความเข้มข้นของก๊าซคาร์บอนไดออกไซด์เพิ่มมากขึ้น อัตราการสังเคราะห์ด้วยแสงสุทธิจะเพิ่มมากขึ้น และพบการตอบสนองของอัตราการสังเคราะห์ด้วยแสงสุทธิต่ออุณหภูมิเพิ่มมากขึ้นด้วย และอุณหภูมิที่เหมาะสมกับค่าอัตราการสังเคราะห์ด้วยแสงสุทธิที่อุณหภูมิที่เหมาะสมนั้นๆ เพิ่มมากขึ้นเช่นเดียวกัน มีแนวโน้มที่จะอิ่มตัวที่ความเข้มข้นของก๊าซคาร์บอนไดออกไซด์มากกว่า 1,200 µmol mol-1 ABSTRACT This research aimed to study the effects of temperature on Para rubber (Hevea brasiliensis Muell. Arg.) leaf photosynthesis rates at different ambient CO2 concentrations by measuring responses of the leaf net photosynthetic rates to the CO2 concentrations in the air at different temperatures in temperature controlled room. The measurement was done using photosynthetically active photon flux at 1,400 µmol m-2 s-1, 50 % to 80 % relative humidity, and nine temperature levels; (10, 15, 22, 28, 32, 36, 40, 42 and 45 ºC). The responses of net photosynthetic rates to leaf temperatures were fitted using the 4th order polynomial equation. Then, the optimum temperatures for the net photosynthetic rate at different CO2 concentration levels were estimated. The result showed that 4th order polynomial equation provided good fit to the responses of the net photosynthetic rates to leaf temperatures. The changes in CO2 concentration influenced the responses. Increased CO2 concentration led to increased net photosynthetic rate and also the responsiveness of net photosynthetic rate to temperature. Finally, optimum temperature increased with CO2 concentration up to approximately 1200 µmol m-2 s-1.